Effect of hydroxyapatite addition on the mechanical strength of glass ionomer cement: Pengaruh penambahan hidroksiapatit terhadap kekuatan mekanis glass ionomer cement - Indriani, Lenni; Balqis, Fatma Paramita; Achmad, Fathul Jihan (Makassar Dental Journal, 2024)
Glass ionomer cement (GIC) is a restorative material with several advantages such as anti-cariogenic properties, biocompati-bility, and natural colour, but has the disadvantage of poor mechanical properties such as low fracture and brittleness. One ap-proach to overcome these drawbacks is to add hydroxyapatite (HA), which has high biocompatibility and a crystal structure simi-lar to human teeth and bone. Over the past few decades, technological developments have introduced materials that are suita-ble for use in various biomedical applications, especially in dentistry. Research shows that HA, extracted from various natural ma-terials, can improve the mechanical properties of GICs; it also retains unique properties such as fluoride release. Thus, the use of HA as an additive in GICs shows significant potential to improve the performance of these dental restorative materials.